Mechanisms of Host Behavioral Change in Toxoplasma gondii Rodent Association - Vyas, Ajai (2015)
The behavioral manipulation hypothesis predicts that parasites can change host behavior in a way that benefits the parasites and not the host (extensively reviewed in [1–9]). In other words, the hypothesis predicts that genes of a parasite can produce an "extended" phenotype that manifests beyond a parasite's soma [10]. Protozoan parasite Toxoplasma gondii (henceforth toxoplasma) is an often-cited example. Chronic toxoplasma infection reduces aversion of rodents to cat odors, plausibly increasing predation by its definitive felid host [11]. Here, I enumerate main narratives that have emerged in the past decade about biological mechanisms of behavioral change in rodents after toxoplasma infection. Cats are infected by toxoplasma when they eat infected prey. The parasite undergoes gametogenesis in cat intestines, resulting in eventual shedding of fecal oocysts that are ingested by intermediate hosts. Entry in the cat is important for the parasite because it permits a) sexual recombination; b) infection of herbivore hosts who otherwise cannot be infected through carnivory between intermediate hosts; and c) the discharge of highly infectious and resilient oocysts into the environment. Yet, entry of the parasite in the cat is constrained by predation rates. Preys of cats avoid cats and cat odors [12]. Apropos, toxoplasma infection leads to reduced aversion of rodents to cat odors [11]. A subset of animals also develops an atypical and “fatal” attraction [11,13]. These behavioral observations suggest, but do not prove, that the parasite creates an extended phenotype in the host behavior. The caution in the preceding sentence is necessary because it is yet unknown if infected rodents are indeed predated more frequently by cats. Toxoplasma is also sexually transmitted through the male ejaculate in rats [14]. Apropos, male rats infected with toxoplasma become more attractive to females [15]. Uninfected females spend greater time near infected males and allow them greater reproductive access [14]. These observations suggest a second parasitic manipulation of the host behavior, whereby being infected creates greater avenues for sexual transmission of the parasite itself [9]. Biological pathways underlying mate choice and innate aversion to predator odor are relatively well-studied in rodents. This has allowed researchers to study proximate mechanisms of parasitic behavioral manipulation in greater detail in this association compared to other host–parasite relationships. This mechanistic research has focused on three main narratives.